Research on Teaching Reform of Numerical Control Programming and Machining in Higher Vocational Colleges Based on the 1+X Certificate System - Dai, Jianhua; Wang, Tao (Education Insights, 2026)
In response to prevalent issues in the Numerical Control Programming and Machining course in higher vocational colleges, such as the disconnection between theory and practice, monotonous teaching methods, and an inadequate evaluation system, this study analyzes the significant role of the "1+X Certificate" system in vocational education. It proposes reform strategies aimed at optimizing the curriculum system, innovating teaching approaches, and refining the evaluation mechanism. The findings indicate that teaching reforms driven by the "1+X Certificate" system can effectively address the dilemmas of traditional instruction, thereby providing a valuable reference for pedagogical innovation in the field of Numerical Control machining within higher vocational education.